Imported scrub typhus: first case in South America and review of the literature - Weitzel, Thomas (Trop Dis Travel Med Vaccines, 2018)
BACKGROUND: Scrub typhus is a neglected vector-borne zoonosis causing life-threatening illnesses, endemic in the Asian-Pacific region and, as recently discovered, in southern Chile. Scrub typhus is rarely reported in travelers, most probably due to the lack of clinical experience and diagnostic tests in non-endemic countries. We report the first case of imported scrub typhus in South America. CASE PRESENTATION: A 62-year-old tourist from South Korea presented severely ill with fever, rash, and eschar in Santiago, Chile. Laboratory exams showed thrombocytopenia and elevated inflammation parameters, hepatic enzymes, and LDH. With the clinical suspicion of scrub typhus, empirical treatment with doxycycline was initiated and the patient recovered rapidly and without complications. The diagnosis was confirmed by IgM serology and by real-time PCR, which demonstrated infection with Orientia tsutsugamushi (Kawasaki clade). CONCLUSIONS: Only due to the emerging clinical experience with endemic South American scrub typhus and the recent implementation of appropriate diagnostic techniques in Chile, were we able to firstly identify and adequately manage a severe case of imported scrub typhus in South America. Physicians attending febrile travelers need to be aware of this rickettsiosis, since it requires prompt treatment with doxycycline to avoid complications.